If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+8-1=-17
We move all terms to the left:
6x+8-1-(-17)=0
We add all the numbers together, and all the variables
6x+24=0
We move all terms containing x to the left, all other terms to the right
6x=-24
x=-24/6
x=-4
| 8u=3/4 | | (3n+2)(n-4)n=5 | | x-1/2+x-1/36+x-1/4=0 | | 1/5.5=x/11 | | 3(6x-9)=45 | | 44=-26+-5q | | 12x-36=3(x-24) | | -3p+2+4p=-3 | | 25=13+6k | | -6-y=-8 | | (7+2х)x(3х+9)=0 | | x/4+12=x | | x+1=-6x-34 | | 5/2/9=45/x | | 6-x=24-10(2x+8)+62+7x | | 2.5x-3.75=1.5x+1.25 | | |2n-3|=15 | | 2u+24=8u | | z8– 2= 1 | | -4.5x=-13.5 | | 4x^2+30x=14 | | 3/x=9/14 | | 3x-3=6x-60 | | 3n=1+9-n | | 14=6+2g | | 5x9-3x=18+15 | | 6y-7=9 | | 2x-3+5=-8 | | -19c-18=-20c | | 3-x/4=13 | | 3/4m+1=10 | | °4x+5=25 |